Gambaran Kualitas Hidup Pasien Diabetes Melitus di RSUD Haji Abdoel Madjid Batoe Kabupaten Batang Hari - Jeni Titi Sari; Dasuki Dasuki; Basok Buhari (STIKes Ibnu Sina Ajibarang, 2025)
DM (Diabetes Militus) has become a health problem in the world because the prevalence of diabetes mellitus continues to increase. Data from the Batanghari Regency Health Office shows that the number of DM patients has increased quite significantly. At the Haji Abdoel Madjid Batoe Regional Hospital, Batang Hari Regency, the number of DM cases reached 351 and the problems encountered were regarding the quality of life, age, gender and duration of the patient's illness and family support. This study aims to determine the characteristics, family support and quality of life of diabetes mellitus patients at the Haji Abdoel Madjid Batoe Regional Hospital, Batang Hari Regency. This research is a quantitative study with a descriptive analytical design or approach. This research was conducted from June 26 to July 11, 2023 in the Inpatient Room and Polyclinic of the Haji Abdoel Madjid Batoe Regional Hospital, Batang Hari. The population in this study were DM patients in January-February 2023 totaling 121 people. The number of samples was 55 respondents. The sampling technique used the accidental sampling technique. Based on the results of the study, it is known that most respondents have a high quality of life (61.8%). It is expected that RSUD Haji Abdoel Madjid Batoe Batang Hari can provide education to DM patients with the aim of maintaining good quality of life for DM patients.